1989
DOI: 10.1113/jphysiol.1989.sp017756
|View full text |Cite
|
Sign up to set email alerts
|

Development of Y‐axon innervation of cortical area 18 in the cat.

Abstract: SUMMARY1. Geniculocortical Y-axons (n = 38) in the optic radiations of 4-5-week-old kittens (n = 20) and adult cats (n = 18) were studied both physiologically and morphologically. Axons were recorded from intracellularly and subsequently filled ionophoretically with horseradish peroxidase (HRP). The HRP filled the axons' terminal arborizations in visual cortex (particularly well for those innervating area 18). Fourteen axons appeared to be completely filled with HRP (n = 8 in kitten, n = 6 in adult) and served… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
1

Year Published

1991
1991
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 67 publications
(110 reference statements)
3
48
1
Order By: Relevance
“…In our earlier study of axons from kittens and normal adult cats, boutons identified at the LM level were a reliable indication of presynaptic sites identified at the EM level (Freund et al, 1985a,b;Friedlander and Martin, 1989). However, it was necessary to make a similar determination for axons in MD cats.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…In our earlier study of axons from kittens and normal adult cats, boutons identified at the LM level were a reliable indication of presynaptic sites identified at the EM level (Freund et al, 1985a,b;Friedlander and Martin, 1989). However, it was necessary to make a similar determination for axons in MD cats.…”
Section: Resultsmentioning
confidence: 96%
“…All quantitative analysis was carried out only on boutons that were fully serially reconstructed as evaluated by collecting full series of sections including the regions with any detectable sign of diameter change in the axon. We have previously demonstrated that boutons visualized at the LM level are sites of synaptic output as seen at the EM level (Freund et al, 1985a,b;Friedlander and Martin, 1989). However, we revalidated this relationship in MD material, and thus we also compared apparent interbouton segments of axon to LM-identified boutons.…”
Section: Methodsmentioning
confidence: 91%
See 3 more Smart Citations